Pengaruh Komitmen Organisasional dan Kepuasan Kerja terhadap Intention to Stay Relawan di Organisasi Non-Profit (Studi pada TurunTangan Malang) - Shalihah, Muthiah (Jurnal Ilmiah Mahasiswa FEB, 2018)
The purposes of this research is to analyze the influence of organizational commitment and job satisfaction on volunteer’s intention to stay in TurunTangan Malang. The type of this research is explanative research with quantitative approach. The sampel of this research are 55 respondents with saturated sampling technique which are active volunteers. Data analysis technique uses multiple linear regression analysis by considering the classical assumption test. The results of this test indicate that organizational commitment and job satisfaction influence simultaneously on volunteer’s intention to stay. For partial influence, only organizational commitment alone has a positive and significant influence on volunteer’s intention to stay  and also becomes the dominant independent variable. While job satisfaction does not significantly influence volunteer’s intention to stay. Key Word : Organizational Commitment, Job Satisfaction, Intention to Stay